In Harm's Way: Children's Work in Risky Occupations in Brazil. (30th June 2015) - DeGraff, Deborah S.; Ferro, Andrea R.; Levison, Deborah
Abstract: There were large numbers of child workers in domestic services, street work, construction and selected areas of agricultural production in Brazil at the turn of the century. These kinds of occupations are often problematic for youth. We show that children engaged in these risky categories of work are more disadvantaged than other employed children and non‐employed children. Results from a large representative survey show that children in 'risky' work are more likely to have parents also engaged in hazardous activities or be living without both parents, characteristics that may be useful for targeting policy. Copyright © 2015 John Wiley & Sons, Ltd.